Effect of intravenous fluid supplementation on drop in serum bilirubin levels in term babies with severe hyperbilirubinemia - Tank, Priyanka; Tank, Rakesh; Singh, Abhishek (International Journal of Contemporary Pediatrics, 2017)
Background: Varied results emerging out of various studies have created a controversy about effect of intravenous fluid supplementation on drop in Serum Bilirubin levels in term babies with severe hyperbilirubinemia. Paucity of literature also warrants this study. The objective of this study is to evaluate the probable effect, if any, of intravenous fluid supplementation in decreasing the serum bilirubin level in healthy term babies with hyperbilirubinemia from Northern India. Methods: In this prospective study healthy term neonates (37-41 weeks gestation) with serum bilirubin (>18 mg/dl and <25 mg/dl) for treatment with phototherapy were randomly allocated to two groups, study group received intravenous fluid for total 16 hours along with breast feed and control group given only breast feeds. Results: Baseline variables like sex distribution, age at admission, gestation, birth weight, admission weight, number of babies, appropriate for gestational age, mode of delivery, oxytocin use, incidence of breast feeding and serum bilirubin level at the time of inclusion in study, were comparable in both control and study group. Drop of total serum Bilirubin (TSB) at 4 hours, 8 hours, 24 hours, 36 hours and 48 hours of study were also significantly higher in study group as compared to control group. Although the drop in TSB level at 60 hours between two groups was not significantly different. Conclusions: Based on our findings it can be concluded that additional intravenous fluid supplementation significantly reduced the serum bilirubin in study group as compared to control group.